High congenital hip dislocation in adults - arthroplasty and functional results - Moura, DL (2020)
Objective: Retrospective case-control study on the authors' experience regarding arthroplasty in high congenital dislocations of the hip in adults. Methods: Sample with 11 high congenital hip dislocations (Hartofilakidis type C) that occurred in seven patients, who were submitted to hip arthroplasty by the same surgeon and with the same surgical technique. Mean follow-up period was 4.32 ± 2.67 years (minimum one year) and all patients were evaluated by the same examiner. Results: All the arthroplasties had cementless fixation, with application of screwed acetabular cups, conical femoral stems, and a metal-polyethylene articular pars. In every patient, shortening femoral osteotomies were performed at subtrochanteric or supracondylar locations. The mean Harris Hip Score at the last evaluation was 88.55 ± 4.50 (range 81-94). The mean time with high dislocation of the hip (42.91 ± 14.59 years, range 19-68) showed a significant inverse correlation with Harris Hip Score (r = 0.80; p = 0.003). All patients reported important relief of pain complaints and are capable of ambulation without any external support. In the unilateral dislocations, leg length discrepancies were fully corrected; in the bilateral cases, isometric limbs were achieved in all patients. All osteotomies consolidated, with a mean interval of 3.27 ± 0.47 months. There were complications in 18.18% of the sample: one iatrogenic intraoperative fracture of the greater trochanter and a transitory sciatic neurapraxia. Conclusion: Despite being a demanding surgery with a reportedly high complication rate, total hip arthroplasty in high congenital dislocations, when properly indicated and technically correctly performed, allows an improvement in function and quality of life.